2022
DOI: 10.24843/eeb.2022.v11.i06.p01
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Tingkat Pendidikan, Distribusi Pendapatan, Dan Pertumbuhan Penduduk Terhadap Kemiskinan Di Kabupaten/Kota Provinsi Bali

Abstract: The problem of poverty is a complex and multidimensional problem. Therefore, poverty alleviation efforts must be carried out comprehensively, covering various aspects of people's lives, and implemented in an integrated manner. This study aims to determine the effect of education level, income distribution, and population growth simultaneously and partially on poverty in the regions/cities of Bali Province, as well as the most dominant variables influencing poverty in the regions/cities of Bali Province. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
(3 reference statements)
1
3
0
4
Order By: Relevance
“…This means that an increase in the HDI should be able to reduce the income inequality that occurs. This is supported by the findings of several previous studies which concluded that HDI has a significant negative effect on income distribution inequality (Samsir & Rahman, 2018;Yanthi & Sutrisna, 2018).…”
Section: Introductionsupporting
confidence: 86%
“…This means that an increase in the HDI should be able to reduce the income inequality that occurs. This is supported by the findings of several previous studies which concluded that HDI has a significant negative effect on income distribution inequality (Samsir & Rahman, 2018;Yanthi & Sutrisna, 2018).…”
Section: Introductionsupporting
confidence: 86%
“…Pembangunan ekonomi adalah suatu proses yang kompleks dan multidimensional yang mencakup berbagai aspek seperti pertumbuhan ekonomi, peningkatan kesejahteraan masyarakat, pembangunan infrastruktur, peningkatan kualitas sumber daya manusia, dan peningkatan akses terhadap layanan kesehatan dan pendidikan. Seiring dengan perkembangan zaman, pembangunan ekonomi menjadi semakin penting dalam meningkatkan kualitas hidup masyarakat (Yanthi & Wenagama, 2022).…”
Section: Pembangunan Ekonomiunclassified
“…Tidak hanya pemerintah, masyarakat juga berperan penting dalam pertumbuhan ekonomi melalui penyerapan tenaga kerja. Jumlah penduduk yang meningkt maka akan memperluas pasar sehingga akan meningkatkan spesialisasi dalam perekonomian (Adipuryanti, 2015). Tenaga kerja yang tinggi akan berdampak positif terhadap pertumbuhan ekonomi apabila lapangan kerja yang tersedia dapat menyerap tenaga kejra, sehingga akan mengurangi pengangguran.…”
Section: Pendahuluanunclassified